Combined effect of neem leaf powder and vermicompost in the management of root-knot nematode disease in Celosia argentea - Atungwu, J. J; Renco, M; Balogun, A. B.; Oladeji, O. A.; Tijjani, I.; Odeleye, H. Y. (ADAN JOURNAL OF AGRICULTURE, 2024)
Due to the rising demand for alternative options for root-knot nematode management, Neem (Azadirachta indica) leaf powder and Vermicompost were tested for their efficacy in controlling this disease in Celosia argentea. An experiment, laid out in Completely Randomized Design, was carried out in the screenhouse. It involved the testing of eight treatments which were replicated four times thus making a total of 32 experimental pots. The trial was repeated once to validate results obtained. Plants were inoculated with 5000 Meloidogyne incognita (Mi) eggs. The experimental pots without Mi egg served as the control. Data were collected on plant height, stem girth, number of leaves, branches and flowers, leaf area index, shoot weight, root weight, dry weight, number of galls, final nematode and egg population and subjected to Analysis of Variance. The New Duncan Multiple Range Test was used to separate statistically significant treatment means. Results showed that the amendments used, reduced the infestation of the treated plants whose final Mi nematode population (2360, 2020, 2050, 1720, 1540, 1230) and egg population (2250, 2030, 2120, 1690, 1540, 1230) which were lower (P d” 0.05) than their initial population (5000 eggs) and when compared to the untreated Mi-inoculated (control) plants which had the highest final population (5858 and 5620) that outnumbered the original inoculum. Neem leaf powder and Vermicompost combined at 1% was statistically at par with other treatments in the reduction of the root-knot disease of C. argentea